‘Mild mannered’? Protest and mobilisation in Portugal under austerity, 2010–2013 - Accornero, G. (2015)
Anti-austerity mobilisations in Southern Europe since 2010 have been widely debated in recent times. Commentators have emphasised the emergence of new political subjects such as the ‘precariat’ organised into loose, IT-connected movements. To what extent do these portrayals reflect the underlying dynamics of this protest cycle, and how do these movements interact with traditional political actors? Using Portugal as a case study, this article maps the cycle of anti-austerity contention between 2010 and 2013 to reveal a more complex picture, where traditional actors, including labour unions and left-wing political parties, emerge as key actors, facilitating and sustaining the discontinuous mobilisation of new forms of activism, while seeking to gain access to new constituencies through them.